1975
DOI: 10.1056/nejm197502272920903
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathogenesis of Syphilitic Glomerulonephritis

Abstract: A renal biopsy was performed on a patient with syphilitic glomerulonephritis characterized clinically by the acute onset of nephrosis that responded dramatically to penicillin therapy. Histologic, electron microscopical and immunohistochemical studies revealed an early membranous glomerulonephritis characterized by the presence of subepithelial basement-membrane deposits containing IgG and C3. The glomerular lesion, however, differed from that in the usual case of membranous nephropathy in that distinctive seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

1976
1976
1991
1991

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(26 citation statements)
references
References 19 publications
0
25
0
1
Order By: Relevance
“…In fact, inhibitory plasma or serum products have been demonstrated in syphilitic patients (Levene et al, 1969;Kantor, 1975) and in T. pallidum infected rabbits (Pavia etal., 1976;1977c). In human syphilitic glomerulonephritis deposits of treponemal antigenantitreponemal antibody complexes have been shown to contribute to tissue injury (Gambol and Reardon, 1975). Although suppressor cells have not been studied in syphilis they could be an important consequence of T. pallidum infection especially in the light of the recent finding of suppressor thymusderived lymphocytes in patients infected with a variety of fungal organisms (Stobo et al, 1976).…”
Section: Proposed Mechanisms Of Immunity In Syphilismentioning
confidence: 99%
“…In fact, inhibitory plasma or serum products have been demonstrated in syphilitic patients (Levene et al, 1969;Kantor, 1975) and in T. pallidum infected rabbits (Pavia etal., 1976;1977c). In human syphilitic glomerulonephritis deposits of treponemal antigenantitreponemal antibody complexes have been shown to contribute to tissue injury (Gambol and Reardon, 1975). Although suppressor cells have not been studied in syphilis they could be an important consequence of T. pallidum infection especially in the light of the recent finding of suppressor thymusderived lymphocytes in patients infected with a variety of fungal organisms (Stobo et al, 1976).…”
Section: Proposed Mechanisms Of Immunity In Syphilismentioning
confidence: 99%
“…10 In the JHR transient acute inflammatory infiltrates are superimposed on the lymphocytic vasculitis.2 Specific antigen-antibody complexes have been observed in early syphilitic nephritis and specific antitreponemal antibodies have been demonstrated in the cutaneous lesions of early syphilis in both man and rabbits.' [1][2][3][4][5][6][7][8][9][10][11][12][13] In non-syphilitic vasculitis of both necrotising and lymphocytic types biopsies of skin lesions have demonstrated immunoglobulins or complement components or both fixed to vessel walls, which may 226 implicate activation of the classic or alternate complement pathways by either immune complexes, endotoxin, or other substances. '4 The intradermal inoculation of T pallidum into rabbits results in changes similar to the naturally occurring disease in man; the rabbit is, therefore, a useful animal model for the study of experimental syphilis.…”
Section: Introductionmentioning
confidence: 99%
“…In antibody elution studies performed on kidney biopsy material, Gamble et al (1975) have demonstrated the presence of antitreponemal antibody within the glomerular deposits. Using an indirect fluorescent antibody technique, Tourville et al (1976) demonstrated the presence of treponemal antigen in the glomerular deposits.…”
Section: Discussionmentioning
confidence: 99%
“…Studies employing electron microscopy and immunofluorescent techniques have demonstrated immune complex deposits on the glomerular basement membrane in syphilitic nephropathy (Falls et al, 1965;Braunstein et al, 1970;Bhorade et al, 1971;Hellier et al, 1971;Kaplan et al, 1972;Yuceoglu et al, 1974). These, together with other studies (Gamble and Reardan, 1975;Tourville et al, 1976), strongly suggest that circulating immune complexes are a pathogenetic factor in the clinical pattern of secondary syphilis. We report a case of secondary syphilis presenting as a nephrotic syndrome in which a kidney biopsy showed deposits in the glomeruli indicating an immune complex nephritis.…”
Section: Introductionmentioning
confidence: 93%